Design of a pin-on-disc-type CNC tribometer including an automotive dry clutch application. (December 2016) - Hoić, Matija; Hrgetić, Mario; Deur, Joško
Highlights: Design of fully computer-controlled pin-on-disc-type tribometer is proposed. Friction interface temperature, normal force and slip speed are feedback controlled. Friction coefficient is directly measured by three-axis piezoelectric force sensor. Innovative suspension for friction sample and force sensor assembly is designed. Tribometer performance is demonstrated via dry clutch friction and wear case study. Abstract: The paper presents the design of a pin-on-disc type tribometer intended for experimental characterization of static and dynamic friction behaviors for various sliding sample pairs. The normal force, slip speed, and temperature, as the main influencing parameters, are precisely controlled during experiments, by applying vertical and rotational servo-axes and an electric heater built in the rotating disc. A compact three-axial piezoelectric force sensor, placed between the vertical-axis screw drive and the friction sample, provides direct measurement of normal and tangential forces used to calculate the sample coefficient of friction. The slip speed is measured directly using an incremental encoder mounted at the rotational table. The disc temperature is measured by a built-in Pt probe, whose wires, together with the heater wires, are connected to the temperature control unit by means of slip rings. The tribometer performances are demonstrated through a study of coefficient of friction, shudder sensitivity, and wear rate characterization for a dry clutch friction material.